Thermodynamics, Gibbs Method and Statistical Physics of Electron Gases Gibbs Method and Statistical Physics of Electron Gases - Askerov, Bahram M.; Figarova, Sophia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book deals with theoretical thermodynamics and the statistical physics of electron and particle gases. While treating the laws of thermodynamics from both classical and quantum theoretical viewpoints, it posits that the basis of the statistical theory of macroscopic properties of a system is the microcanonical distribution of isolated systems, from which all canonical distributions stem. To calculate the free energy, the Gibbs method is applied to ideal and non-ideal gases, and also to a crystalline solid. Considerable attention is paid to the Fermi-Dirac and Bose-Einstein quantum statistics and its application to different quantum gases, and electron gas in both metals and semiconductors is considered in a nonequilibrium state. A separate chapter treats the statistical theory of thermodynamic properties of an electron gas in a quantizing magnetic field.
Basic Concepts of Thermodynamics and Statistical Physics -- Law of Thermodynamics: Thermodynamic Functions -- Canonical Distribution: Gibbs Method -- Ideal Gas -- Non-Ideals Gases -- Solids -- Quantum Statistics: Equilibrium Electron Gas -- Electron Gas in Quantizing Magnetic Field -- Non-Equilibrium Electron Gas in Solids.
Keywords: Physics; Quantum theory; Mathematical physics; Thermodynamics; Physics; Thermodynamics; Mathematical Methods in Physics; Quantum Physics; Statistical Physics, Dynamical Systems and Complexity